Corporate Private Information and Credit Ratings: Evidence from Corporate Geographic Distance. Issue 11 (2nd September 2022) - Gu, Qiankun; Lin, Wanfa; Sheng, Yan; Wang, Haoyu
ABSTRACT: This paper uses the geographic distance between corporate locations and headquarters of credit rating agency as a proxy for corporate private information acknowledged by rating agency, to investigate the effect of corporate private information on its credit ratings. Our samples include the Chinese institutional and corporate bond's credit ratings from 2008 to 2018. Results indicate the geographic distance is negatively associated with the corporate private information accessed by rating agency, leading to a higher information asymmetry, worse institutional and corporate bonds' credit rating and lower quality of the rating information content. Results remain solid and significant after controlling for the implicit guarantee of the government, corporate public information, ownership structure and analysts' skills. We find corporate private information generates more values for corporates whose information environments are more complex, reflected in more business segments and less covered analysts. We also find the open of high-speed railway in China facilitates rating agency's access to corporate private information, thus reducing the impact of geographic distance, while the lockdown periods of Covid-19 pandemic in China suddenly increase the cost of collecting private information and thus aggravating the distance effect.